Respuesta :

Answer:

x=-4 and x=1/2

Step-by-step explanation:

The formula to solve a quadratic equation of the form

[tex]ax^{2} +bx+c=0[/tex]

is equal to

[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]

in this problem we have

[tex]2x^{2} +7x=4[/tex]  

equate to zero

[tex]2x^{2} +7x-4=0[/tex]  

so

[tex]a=2\\b=7\\c=-4[/tex]

substitute in the formula

[tex]x=\frac{-7(+/-)\sqrt{7^{2}-4(2)(-4)}} {2(2)}[/tex]

[tex]x=\frac{-7(+/-)\sqrt{81}} {4}[/tex]

[tex]x=\frac{-7(+/-)9} {4}[/tex]

[tex]x=\frac{-7(+)9} {4}=\frac{1}{2}[/tex]

[tex]x=\frac{-7(-)9} {4}=-4[/tex]

therefore

The solutions are

x=-4 and x=1/2